Affinity of new anticancer agent, DB-174, to membranes and HSA determined by fluorescence spectroscopy methods - Kruszewski, Stefan; Bom, David; Ziomkowska, Blanka; Cyrankiewicz, Michał (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
The application of fluorescence spectroscopy methods to determining the properties of camptothecins – promising anticancer agents – are described in this paper. The fluorescence anisotropy measurements provide useful information about the binding of camptothecin and its analogues to cell membranes and human serum albumin (HSA) that is important for potential clinical applications of these agents, and permits the selection from many camptothecin analogues those ones exhibiting desirable biomedical properties. Binding properties of 7-trimethylsilyl-ethyl-10 hydroxy-camptothecin are the subject of this paper.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 199-207
Keywords: optyka; camptothecin; fluorescence anisotropy; membranes; human serum albumin (HSA)